2011
DOI: 10.1055/s-0030-1270450
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Variability in Women with Anovulatory and Ovulatory Polycystic Ovary Syndrome, and Normal Controls

Abstract: Women with polycystic ovary syndrome (PCOS) were found to have a higher biological variability in insulin resistance (IR) compared to controls, but it is unknown whether this variability in IR differs between PCOS who are anovulatory compared to those who have an ovulatory cycle. The primary aim of this study was to compare and contrast the variability of IR in women with ovulatory and anovulatory PCOS, in comparison to normal subjects. 53 Caucasian women with PCOS and 22 normal ovulating women were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…PCOS women were signifi cantly younger, had higher fasting insulin levels, HOMA-IR, ratio total cholesterol-to-HDL (QChol/HDL), testosterone, androstenedione levels and signifi cantly lower SHBG and HDL levels. Median Ferriman-Gallwey score of PCOS women was 7 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and 52 % of PCOS women were hirsute. Oligo-or amenorrhoea was present in 475 out of 545 PCOS women (87 %) and polycystic ovaries were found in 264 women (48 %).…”
Section: Discussionmentioning
confidence: 99%
“…PCOS women were signifi cantly younger, had higher fasting insulin levels, HOMA-IR, ratio total cholesterol-to-HDL (QChol/HDL), testosterone, androstenedione levels and signifi cantly lower SHBG and HDL levels. Median Ferriman-Gallwey score of PCOS women was 7 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and 52 % of PCOS women were hirsute. Oligo-or amenorrhoea was present in 475 out of 545 PCOS women (87 %) and polycystic ovaries were found in 264 women (48 %).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated a relationship between PCOS and both development and persistence of IR despite of control of PCOS-induced hormonal disturbances as indicated by being pregnant. In line with these findings, Wang et al (25) found women with a history of recurrent pregnancy loss (RPL) are at an increased risk for IR during the first trimester of a new pregnancy and Cho et al (26) reported that IR and PCOS are coincident events despite of the higher and more variable score in women with anovulatory than women with ovulatory PCOS. Also, Celik et al (27) documented that compared with the control group; patients with RPL were more likely to have IR.…”
Section: Discussion:-mentioning
confidence: 83%
“…It has been shown that IR is present more often in the classic phenotype (80.4%) than in the ovulatory (65.0%) and normoandrogenic (38.1%) [34]. Moreover, it is more frequent in patients with anovulatory compared to those with ovulatory cycles in PCOS [35].…”
Section: The Pathomechanism and Role Of Ir In Pcosmentioning
confidence: 99%